EFFECT OF PROBIOTIC GIVING SACCHAROMYCES spp. Gb-7 and Gb-9 IN THE RANGE OF EGG PRODUCTION CHICKEN LOHMANN BROWN AGE 40-48 WEEK - I K., Sujana; Candrawati, D. P. M. A.; Bidura, I G. N. G. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This research was carried out to determine the effect of giving probiotics 0.3% Saccharomyces spp. Gb-7 and Gb-9 in rations on chicken egg production Lohmann Brown phase age 40-48 weeks. This research was carried out by farmers in Dajan Peken Village, Tabanan for 2 months. The design used in this study was Completely Randomized Design (CDR) with three treatments and six replications. The third treatments were chicken giving rations without probiotics as control (A); chickens given ration with the probiotic Saccharomyces spp . Gb-7 0.3% (B); and chickens given ration with the probiotic Saccharomyces spp . Gb-9 0.3% (C). The variables observed in this research were ration consumption, drinking water consumption, total egg weight, total number of eggs and FCR. The results showed chickens given ration with probiotics Saccharomyces spp. Gb-7 and Gb-9 that total egg weight and FCR chickens given probiotics Saccharomyces spp. Gb-7 and Gb-9 each had a significant (P<0.05) but on ration consumption, drink water consumption, and the number of eggs each had a non significant (P>0.05). From the results of this research it can be concluded that the granting of 0.3% of the probiotic Saccharomyces spp . Gb-7 and Gb-9 in ration Lohmann Brown can provide significant influence to the total weight of the egg and the FCR had non significant influence towards the consumption of rations, drinking water consumption, and the total number of eggs Lohmann Brown age 40-48 weeks. Keywords: Egg production, Lohmann Brown, Probiotics, Saccharomyces spp .